Relaparotomy after caesarean section: a retrospective observational study in a tertiary medical college - Das, Rumpa; Sarkar, Malay; Roy, Debobrata; Das, Krishnapada; Pramanik, Arpita; Murmu, Marshal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Relaparotomy is the term which defines operations performed within 60days after the initial surgery. Ralaparotomy following caesarean section may happen and that’s why a study was done to evaluate the risk factors, indications, procedures done during relaparotomy after caesarean section. Methods: A retrospective observational study was conducted in the department of obstetrics and gynaecology in burdwan medical college and hospital for a period of 3years from 1June 2019 to 31 May 2022. Total 32 cases required relaparotomy following caesarean section. Results: In this study, there were 25,527 caesarean deliveries out of 56,145 total deliveries over 3years time period. Among caesarean deliveries 32 cases underwent relaparotomy (0.12%). In most of the cases relaparotomies were due to intraperitoneal haemorrhage, rectus sheath hematoma, postpartum haemorrhage. Indications of cesarean section were severe preeclampsia, non-progress of labour, abruption, post cesarean section with scar tenderness, meconium-stained liquor with fetal distress. Most of the women were in the age group of 20-30 years. Resuturing of the bleeding points were done in most of the cases. Conclusions: As a lifesaving procedure, decision of relaparotomy should be taken as soon as possible. Proper hemostasis need to be ensured before closure of abdomen, as intraperitoneal haemorrhage is the most common indications for relaparotomy.